TINJAUAN EFISIENSI USAHA HOME INDUSTRI PECI DI KEBUMEN - Siti Muntahanah; Harsuti Harsuti (FEB UNWIKU PURWOKERTO, 2020)
The purpose of this research is to find out whether the business done by the peci home industry in Bandung Kebumen village is efficient? This research was conducted with the population is the cap business actor in Bandung Kebumen, amounting to 40, and the research sample was taken by purposive sampling, namely the sample was drawn from a certain number of the population using certain considerations or criteria, namely the turnover per day produces a minimum of 5 scores. This research shows that the Small and Micro Enterprises engaged in the Home Industry Peci in Bandung Sruni Kebumen in 2016 in carrying out their production activities are efficient, this can be seen from the Benefit Cost Ratio obtained from some of the Peci Home Industry business players at a number above 1 , which is in the range of 1,271 to 1,325. The business of making peci in Bandung is mostly a supporting business besides being a farmer, so that even though the sales system is seasonal and payments are made on time, it does not disturb the economy of these business actors, because they can fulfill their daily activities from investment in the agricultural sector.